Model Diversi terhadap Anak Pelaku Tindak Pidana Pencurian dengan Pemberatan dalam Sistem Peradilan Pidana Anak untuk Mewujudkan Kepastian Hukum - James Tanardi Febrianto; Ismail; Dewi Iryani (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This research examines the tension between legal ideality and the empirical reality of implementing Restorative Justice for children who commit theft under aggravating circumstances (pencurian dengan pemberatan). Normatively, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law) and its derivative regulations establish Restorative Justice-based diversion as the primary approach to protect the best interests of the child and avoid stigmatization. In practice, however, the application of diversion for aggravated theft (Article 363 of the old Criminal Code or Article 477 of the new Criminal Code) is constrained by the